You are on page 1of 6

In questions 1) through 9) determine the derivative. (Simplify where possible.

x4
1) f ( x) = x e 2 x
2) f ( x) = 3) f ( x) = sec( x 2 )
1 + x2

x 2 sin x
4) f ( x) = 5) f ( x ) = e x csc x 6) f ( x) = cos6 ( x 4 )
1+ x

sec x sin( x 2 + 1)
7) f ( x) = 8) f ( x) = e tan( x )
9) f ( x) =
1 + tan x x4

1− x
10) Let f ( x) = and g ( x) = sin x .
1 − x2

a) What is lim f ( x) ? (Justify your answer!)


x→4

b) Use appropriate limits to determine the asymptotes of the function f (x) .


π
c) What is ( f  g )( x) , if 0 < x < ? Write your answer without using fractions.
2

2 x 3 − 4 x<2
11) Suppose f ( x) =  .
 kx x≥2
a) Write down the definition of continuity of a function f (x) at x = 2?
b) What is k so that f (x) is continuous at x = 2?

x2
12) Suppose f ( x) = . Where is f (x) continuous? (Justify your answer!)
x2 − 4

13) Suppose r is any real constant. What is the 50th derivative of f ( x) = e r x ?

14) a) Determine f ′(x) and f ′′(x) for f ( x) = x sin(π x) .

b) For the function in part (a), what is the equation of the line tangent to the graph of f (x)
at x = 1/2.

MATH.1310 Exam 2 Review Problems


−1
3 x +1 = 5 . = 2.
3
15) a) Solve for x: b) Solve for x: ex

16) Solve for x: log 5 ( x − 3) = 4 . b) Solve for x: log 4 ( x − 3) = log 4 x − 1 .

dy
17) Find if a) x 2 y + ln y = 0 b) x 2 sin −1 ( y ) + e − x = y 2
dx
18) Using the limit definition of the derivative calculate f ′(x) for f ( x) = 2 x 3 + x 2 .

1
19) Using the limit definition of the derivative calculate f ′(x) for f ( x) = .
x

20) Suppose f ( x) = x 2 + 1 . Find the average rate of change of f (x) on [0, 3]

x
21) Suppose f ( x) = . Find the average rate of change of f (x) on [1, 5]
x − 4x + 1
2

MATH.1310 Exam 2 Review Problems


22) Graph the function f ( x) = 2 for − 4 ≤ x ≤ 0 , and the function g ( x) = log 2 ( x + 1) for
−x

0 ≤ x ≤ 7 . Label 3 points on each graph. The graphs must fit in the grid.

20

18

16

14

12

10

-10 -8 -6 -4 -2 0 2 4 6 8 10

MATH.1310 Exam 2 Review Problems


Solutions:

x 3 (2 x 2 + 4)
1) f ′( x) = xe (2 + x)
x
2) f ′( x) =
(1 + x 2 ) 2

2 x sin x + x 2 sin x + (1 + x) x 2 cos x


3) f ′( x) = 2 x sec( x ) tan( x )
2 2
4) f ′( x) =
(1 + x 2 ) 2

5) f ′( x ) = (1 − x cot x) csc xe f ′( x) = −24 x 3 cos 5 ( x 4 ) sin( x 4 )


x csc x
6)

sec x(tan x − 1) sec 2 ( x )e tan( x)

7) f ′( x) = 8) f ′( x ) =
(1 + tan x) 2 2 x

2 x 2 cos( x 2 + 1) − 4 sin( x 2 + 1)
9) f ′( x) =
x5

1
10) a) lim f ( x) = using Direct Substitution Property
x→4 5

b) xlim f ( x) = 0 = lim f ( x) y = 0 is a horizontal asymptote.


→∞ x → −∞

For vertical asymptotes only possibilities are x = ±1 .


1
lim f ( x) = so x = 1 is not a vertical asymptote.
x →1 2
lim+ f ( x) = ∞ and lim− f ( x) = −∞ , so x = −1 is a vertical asymptote.
x → −1 x → −1

c) ( f  g )( x) = sec x(sec x − tan x)

11) a) f (2) = lim f ( x) b) k = 6


x→2

x2 a2
12) Since f ( x) = 2 is a rational function, we have lim f ( x) = 2 = f (a ) (using
x −4 x→a a −4
x2
the direct substitution property) as long as we are in the domain of f ( x) = 2 which is
x −4
x ≠ ± 2 . So the function is continuous at x ≠ ± 2 . Clearly if x = ± 2 the function is
undefined, and hence discontinuous.

MATH.1310 Exam 2 Review Problems


13) f
( 50 )
( x) = r 50 e rx

14) a) f ′( x) = sin(π x) + π x cos(π x) f ′′( x) = 2π cos(π x) − π 2 x sin(π x)

b) y = x

15) a) x = log3 5 − 1 b) x = 3 ln 2 + 1 16) a) x = 628 b) x = 4

−x
2 xy 2 e − x − 2 x sin −1 ( y ) (e − 2 x sin −1 ( y )) 1 − y 2
y′ = =
17) a) y ′ = − 2 b) x2 x2 − 2y 1− y2
x y +1 − 2y
1− y 2

18) f ( x) = 2 x 3 + x 2

f ′( x) = lim
f ( x + h) − f ( x )
= lim
( ) (
2( x + h)3 + ( x + h) 2 − 2 x 3 + x 2 )
h→0 h h→0 h

= lim
(6 x h + 6 xh
2 2
)
+ 2h 3 + 2 x h + h 2
( )
= lim 6 x 2 + 6 xh + 2h 2 + 2 x + h = 6 x 2 + 2 x
h→0 h h→0

1
19) f ( x) =
x
 1   1 
 − 
f ( x + h) − f ( x )  x+h   x 
f ′( x) = lim = lim
h→0 h h→0 h

 x − x+h   x − x+h 
   
 x+h x   x + h x ( x + x + h )
= lim   = lim  
h→0 h h→0 h( x + x + h )

 x − ( x + h) 
 
= lim  x+h x 
= lim
(− h )
h → 0 h( x + x + h ) h → 0 h( x + x + h ) x + h x
−1 −1
= lim =
h→0 ( x + x + h ) x + h x 2 x3

10 − 1 1
20) 21)
3 3

MATH.1310 Exam 2 Review Problems


20

18

(−4, 16)

16

f (x) 14

12

10

(−3, 8) 8

6
g (x)
(−2, 4)
4

(3, 2)
(7, 3)
(−1,2) 2

(0, 1) (1, 1)

22) -10 -8 -6 -4 -2 0 2 4 6 8 10
(0, 1)

MATH.1310 Exam 2 Review Problems